Формування лідерських якостей здобувачів освіти у виховному процесі закладів загальної середньої освіти. - Ємчук, Тетяна Володимирівна; Чубрей, Олександра Степанівна (Центральноукраїнський державний педагогічний університет імені Володимира Винниченка, 2022)
The article analyzes the formation of leadership qualities of students in the educational process of general secondary education institutions. Emphasis is placed on society's need for sociable leadership personalities that must be nurtured from childhood. After all, who this person will become in the future depends on the upbringing process. Therefore, the topic of leadership attracts the attention of representatives of various directions. Research on the education of leadership qualities of an individual does not give a holistic view of the project activity of education of these qualities. The main qualities of a leader include: responsibility, demandingness in the performance of work in relation to oneself and people; honesty before oneself and people; empathy (to feel empathy); able to influence others; communicativeness; organized in any spheres of life; is able to demonstrate a personal example in behavior and activity; self-confidence; able to manage himself and his own emotions; ready to make responsible decisions. Special attention should be paid to the analysis of diagnostics of communicative and organizational abilities according to the method of V.V. Sinyavskyi and B.O. Fedoryshyn The communicative and organizational abilities of higher education students were investigated and identified, which include the rapid establishment of relationships between people, the establishment of business contacts, their participation and involvement in public and group events, initiative, the ability to take responsibility and influence people or the group as a whole. directs their activities in a certain direction, which contributes to the achievement of common goals. The conducted research does not cover all aspects of the problem. The development of modern interactive forms, methods of formation of leadership qualities, education seekers in institutions of general secondary education requires further scientific study. Taking into account the relevance of the researched topic, it is possible to recommend: introduce trainings, electives or optional courses into the educational activities of general secondary education institutions. Such a set of activities for the development of leadership qualities in students of education should contain group and tasks for diagnosis, development and improvement of personal leadership qualities.
THE FORMATION OF LEADERSHIP QUALITIES OF EDUCATION ACQUISITIONS IN THE EDUCATIONAL PROCESS OF HALL SECONDARY EDUCATION INSTITUTIONS
Keywords: комунікативні і організаторські схильності; здобувачі освіти; лідер; виховний процес; лідерські якості